Analysing trajectories of vegetation and landscape change in southern Africa from historical field photographs. (December 2020) - Knight, Jasper; Fitchett, Jennifer
Abstract: Examining vegetation change over decadal to centennial timescales by comparing paired sets of historic and contemporary field photographs is a tried and tested approach, used recently in many ecological studies in southern Africa. This approach, however, fails to consider the different forcing factors contributing to vegetation and landscape change over historical time periods. This Viewpoint article outlines some limitations of the analytical approaches used in such studies, and problems of reconciling different datasets related to climate, ecosystems and land management in rapidly changing landscapes. We propose an alternative and integrated methodology for analysing spatial and temporal patterns of historical vegetation change using such datasets, based on a systematic checklist of key criteria related to the landscape under examination, and the mode of photography used. The proposed methodology provides a standardized and reproducible approach that can overcome the limitations of historical photographic analysis of vegetation changes.